Refining the Candidate Environment: Interpersonal Stress, the Serotonin Transporter Polymorphism, and Gene-Environment Interactions in Major Depression. (May 2014) - Vrshek-Schallhorn, Suzanne; Mineka, Susan; Zinbarg, Richard E.; Craske, Michelle G.; Griffith, James W.; Sutton, Jonathan; Redei, Eva E.; Wolitzky-Taylor, Kate; Hammen, Constance; Adam, Emma K.
Meta-analytic evidence has supported a gene-environment interaction between life stress and the serotonin transporter–linked polymorphism (5-HTTLPR) on depression, but few studies have examined factors that influence detection of this effect, despite years of inconsistent results. We propose that the candidate environment (akin to a candidate gene) is key. Theory and evidence have implicated major stressful life events (SLEs)—particularly major interpersonal SLEs—as well as chronic family stress. A total of 400 participants from the Youth Emotion Project (which began with 627 high school juniors oversampled for high neuroticism) completed up to five annual diagnostic and stress interviews and provided DNA samples. A significant gene-environment effect for major SLEs and S -carrier genotype was accounted for significantly by major interpersonal SLEs but not significantly by major noninterpersonal SLEs. S -carrier genotype and chronic family stress also significantly interacted. Identifying such candidate environments may facilitate future gene-environment research in depression and psychopathology more broadly.